Clinical characteristics of itch in cutaneous lupus erythematosus: A prospective, multicenter, multinational, cross-sectional study. (August 2021) - Samotij, Dominik; Szczęch, Justyna; Antiga, Emiliano; Bonciani, Diletta; Caproni, Marzia; Chasset, François; Dańczak-Pazdrowska, Aleksandra; Furukawa, Fukumi; Hasegawa, Minoru; Hashizume, Hideo; Ikeda, Takaharu; Islam, Aminul; et al.
Objective: Pruritus is an important symptom frequently accompanying various inflammatory skin conditions and some recent data indicated that it may be associated with autoimmune connective tissue diseases. The aim of this study was to assess the frequency and clinical presentation of itch in CLE. Methods: A multinational, prospective, cross-sectional study was performed to assess the prevalence, intensity and clinical characteristic of pruritus in various subtypes of CLE. A total of 153 patients with active CLE lesions were included. Their age ranged between 17 and 82 years (mean 49.8 ± 15.4 years), and 115 patients (75.2%) were women. The disease activity and damage were assessed according to the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI). Pruritus severity was assessed with Numeric Rating Scale (NRS) and the 12-Item Pruritus Severity Scale. Dermatology Life Quality Index and EQ-5D questionnaire were used to measure quality of life. Results: Pruritus was present in 116 (76.8%) of patients of whom half had NRS scoring equal or above 4 points indicating moderate or severe pruritus. Most commonly itch was localized on the scalp, face (excluding ears and nose) and arms (40.5%, 36.2%, 31.9%, respectively). Sensations connected with pruritus were most frequently described as burning, tingling and like ants crawling feeling, but 31.9% patients described it as "pure itch". More than half of patients reported that pruritus was present every day, and it was most frequent during the evenings. The pruritus scoring and the CLASI activity score were significantly correlated (r = 0.42, p = 0.0001), while no correlation was found with the CLASI damage score (p = 0.16). Both the maximum and average itch intensity were correlated with systemic lupus erythematosus (SLE) activity measured with the Systemic Lupus Erythematosus Disease Activity Index. Conclusions: Pruritus is a common, but frequently overlooked symptom of CLE. Its intensity correlates with the activity of CLE, but not with the skin damage. In more than a half of patients it occurs on a daily basis. The correlation between the intensity of pruritus and the activity of the skin lesions and the systemic involvement indicate that pruritus could be an individual indicator of both SLE and CLE activity.